Strategi pemilihan media sebagai sarana komunikasi pemasaran pada wisata kota surabaya - Hermanto, Yustinus Budi; Tresyanto, Citra Anggraini (Jurnal Komunikasi Profesional, 2021)
Abstract The diversity of tourism objects owned by the city of Surabaya makes the city of Surabaya as one of the cities in Indonesia that is worthy to be visited with tourist destinations of various ages ranging from children to adult visitors. The diversity of tourism objects owned include Nature Tourism, Educational Tourism, Religious Tourism, and City Tourism. The existence of tourist attractions in the city of Surabaya must be published to the public with the main goal of attracting visitors to come for tours. To be able to publish it, media facilities are needed to support the marketing communication process. This study focuses on the strategy of selecting media as a marketing communication to introduce Surabaya City tourism objects. This research is qualitative with descriptive design. This study aims that the selection of communication media is carried out in appropriate stages so that the aim is to introduce the tourism object of Suarabaya City to the whole community and be able to attract visitors to travel.